AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN SPEAKING ENGLISH AT GRADE X OF SMA PERSADA BANDAR LAMPUNG - Novia Arnanda; Harpain Harpain (LINGUISTIKA, 2017)
The objectives of this research were to know what is the most difficult aspect that the students encounter in speaking, and to see what are the causes in students’ difficulties that face the students while they are speaking English.In this research, I used the descriptive qualitative method. The kind of method was used the feel the experience the real world, and also to know people’s points of view of a certain phenomena. It was also used to obtain the truthful, presice, and well-organized explanation about students’ dificulties in speaking English. This reserach was done at grade X.1 of SMA Persada Bandar Lampung that consisted of 22 students. To gather the data, I did observation, gave questionnaire, and interview. The data was analyzed by combining the results of observation, questionnaire, and interview in some table, graphic, and also pharagraph.The results of this research showed that there ase some difficulties that the students faced when spoke English in the class, from the questionnaire result also showed mostly positif and negatif feedbacks that were so hard for them to speak English. The combination of those three instruments is able to be the way to know what are the students’ problems that were so hard for them to speak English.